Reparations and peacebuilding: issues and controversies - Firchow, Pamina (Human rights review, 2013)
This introduction to our special section of Human Rights Review on Reparations and Peacebuilding gives an overview of the challenges currently confronting both peacebuilding and reparations. The special section aims to explore the relationship between these two mechanisms and examines the role that reparations schemes can play in salving or exacerbating conflict.